Manganese(I)‐Catalyzed Regio‐ and Stereoselective 1, 2‐Diheteroarylation of Allenes: Combination of C−H Activation and Smiles Rearrangement. Issue 33 (5th July 2017) - Chen, Shi‐Yong; Han, Xiang‐Lei; Wu, Jia‐Qiang; Li, Qingjiang; Chen, Yunyun; Wang, Honggen
Abstract: Heteroarenes are important structural motif in functional molecules. A Mn I ‐catalyzed 1, 2‐diheteroarylation of allenes via a C−H activation/Smiles rearrangement cascade is presented. The reaction occurred under additive‐free or even solvent‐free conditions, which allowed the creation of two C−C and one C−N bonds in a single operation. A series of structurally diverse bicyclic or tricyclic compounds bearing an exocyclic double bond were constructed in good to excellent efficiency. The decarboxylative ring‐opening of the products led to the facile synthesis of vicinal biheteroaryls. Synthetic applications were demonstrated and preliminary mechanistic studies were conducted. Abstract : Diheteroarylation of allenes : A Mn I ‐catalyzed C−H activation/Smiles rearrangement cascade enabled an unprecedented 1, 2‐diheteroarylation of allenes. The reaction occurred under additive‐free or even solvent‐free conditions. A series of diverse bicyclic or tricyclic compounds bearing a valuable exocyclic double bond were constructed. The decarboxylative ring‐opening of the products led to the facile synthesis of vicinal biheteroaryl compounds.